ANALISIS DAN PERANCANGAN SISTEM INFORMASI ADMINISTRASI GEREJA PADA GEREJA HKBP KAMAL RAYA RESSORT CENGKARENG - Ferry Stephen Natahnael Bagindo (Institut Bisnis dan Informatika Kwik Kian Gie, 2016)
In terms of the administration of the church need something that can support the activities of the administrative information storage which aims to save any documents neat church administration , church usually still apply conventional terms because they are already familiar with it although it is a long time in processing such data .Information Systems Administration HKBP Kamal Raya created with VB.NET and database programming using Microsoft Access for database . The author uses VB.NET so that authors can create applications that are easily understood by users of the secretariat of the church .In this study , data collection was done by direct interview kepad Parharetaon Church . Church Kamal Raya HKBP ressort Cengkareng still conventional in the church of recording admsinistratrationThis study resulted in an information system, a functioning church administration for registering all forms of administration in the church congregation HKBP Kamal Raya ressort Cengkareng From this study it can be concluded that the information system is used very helpful in recording and administration of data search congregation , and advice in the future is to build an integrated system between HKBP around the world so that there is no duplication of data in another church.Â Keywords : Information Systems, Administration, Church